Methyl 1-{4-[(S)-2-(methoxycarbonyl)-pyrrolidin-1-yl]-3,6-dioxocyclohexa-1,4 -dien-1-yl}pyrrolidine-2-carboxylate - Garden, S.J.; Skakle, J.M.S.; Tiekink, E.R.T.; Wardell, J.L. (International Union of Crystallography, 2010)
The complete molecule of the title diproline ester quinone, C(18)H(22)N(2)O(6), is generated by a crystallographic twofold axis, which passes through the centre of the benzene ring. Both -CO(2)Me groups are orientated to the same side of the benzene ring, with the carbonyl groups pointing roughly towards each other. The conformation of the proline residue is an envelope. In the crystal, a three-dimensional network is sustained by C-H center dot center dot center dot O interactions involving both the quinone and carbonyl O atoms.